2020
DOI: 10.1002/jso.26072
|View full text |Cite
|
Sign up to set email alerts
|

Surgical drain placement in distal pancreatectomy is associated with an increased incidence of postoperative pancreatic fistula and higher readmission rates

Abstract: BackgroundPostoperative pancreatic fistula (POPF) can result in significant morbidity after distal pancreatectomy (DP). It is common practice to place prophylactic surgical drains during DP to monitor and minimize POPF complications; however, their use is controversial.ObjectiveThe aim of this study is to determine if drainage helps to prevent adverse outcomes and decrease the need for additional interventions after DP.MethodsAll patients who underwent DP without vascular resection were identified in the 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Mangieri et al . 16 reported a higher rate of POPF grade B/C and readmissions in the drain group. Behrman and co-workers 14 reported no difference between groups in severe morbidity and grade B/C POPF.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Mangieri et al . 16 reported a higher rate of POPF grade B/C and readmissions in the drain group. Behrman and co-workers 14 reported no difference between groups in severe morbidity and grade B/C POPF.…”
Section: Discussionmentioning
confidence: 87%
“…Pooled analysis showed that the POPF rate was lower in the no-drain group compared with the drain group (RR 0.55, 0.42 to 0.72). Readmissions were reported in three studies 1 , 16 , 17 , with a lower rate in the no-drain group (RR 0.76, 0.60 to 0.96).…”
Section: Resultsmentioning
confidence: 98%
“…An evaluation of 1,158 patients undergoing distal pancreatectomy found a higher rate of POPF in the "drain group" compared to the "no drain group" (19.4% vs 6.9%, respectively; P ¼ .001). 25 A multicenter randomized trial including 344 patients found no difference in clinically relevant POPF rates between patients undergoing distal pancreatectomy with or without a drain in situ. Percutaneous drain placement and reoperation and readmission rates did not differ between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Behrman et al ( 48 ) concluded that placement of drains following elective distal pancreatectomy was associated with a higher overall morbidity and pancreatic fistulas. Mangieri et al ( 49 ) found a significant increase in the rates of readmission with the placement of surgical drain after DP. In the current study, we found that there was no significant difference between the drain group and the no-drain group in terms of mortality and morbidity, as well as bile leak, hemorrhage, DGE, intra-abdominal abscess, IR and reoperation.…”
Section: Discussionmentioning
confidence: 99%